Blowing Out the Candle: How to Quench Galaxies at High Redshift—An Ensemble of Rapid Starbursts, AGN Feedback, and Environment - Lucas C. Kimmig; Rhea-Silvia Remus; Benjamin Seidel; Lucas M. Valenzuela; Klaus Dolag; Andreas Burkert (The Astrophysical Journal)
Recent observations with JWST and the Atacama Large Millimeter/submillimeter Array have revealed extremely massive quiescent galaxies at redshifts of z = 3 and higher, indicating both rapid onset and quenching of star formation. Using the cosmological simulation suite Magneticum Pathfinder, we reproduce the observed number densities and stellar masses, with 36 quenched galaxies of stellar mass larger than 3 × 10 ^10 M _⊙ at z = 3.42. We find that these galaxies are quenched through a rapid burst of star formation and subsequent active galactic nucleus (AGN) feedback caused by a particularly isotropic collapse of surrounding gas, occurring on timescales of around 200 Myr or shorter. The resulting quenched galaxies host stellar components that are kinematically fast rotating and alpha-enhanced, while exhibiting a steeper metallicity and flatter age gradient compared to galaxies of similar stellar mass. The gas of the galaxies has been metal enriched and ejected. We find that quenched galaxies do not inhabit the densest nodes, but rather sit in local underdensities. We analyze observable metrics to predict future quenching at high redshifts, finding that on shorter timescales <500 Myr, the ratio M _bh / M _* is the best predictor, followed by the burstiness of the preceding star formation, t _50 – t _90 (time to go from 50% to 90% stellar mass). On longer timescales, >1 Gyr, the environment becomes the strongest predictor, followed by t _50 – t _90 , indicating that at high redshifts the consumption of old gas and lack of new gas are more relevant for long-term prevention of star formation than the presence of a massive AGN. We predict that relics of such high- z quenched galaxies should best be characterized by a strong alpha enhancement.